Determination Aspects of Possible Purchasing Prices for Blue Mussel Products from the Baltic Sea - Ozoliņa, Zaiga; Sloka, Biruta (Journal of Economics and Management Research, 2019)
Demand for marine products has been relatively high and is increasing in most of countries. With higher demand for higher-value and protein-rich products population is looking for other sources that could be protein-rich products and might be substitute for fish products. Blue mussel contains proteins and minerals therefore it might become as food and feed ingredient and supplement product for food. Experience in many countries world-wide where mussel production is more developed has indicated that important aspect in realisation of the production is effective marketing. The following research methods were used in the research: studies of scientific publications on blue mussel price and factors influencing the price, survey of different stakeholders in mussel farming – public administrators, entrepreneurs and researchers; expert interviews. The data obtained from the study were analysed by indicators of descriptive statistics, cross – tabulations, testing of statistical hypothesis with t–test and analysis of variance – ANOVA, as well as correlation analysis and one of the most applied multivariate analysis methods – factor analysis. Based on experts’ survey the results indicated that experts are ready to pay more for fresh mussel rather for than for frozen mussel. The most of expert’s answers indicated the purchase price 5 euros for kilogram of frozen blue mussel.
Keywords: price; blue mussel; survey of stakeholders; marketing; the Baltic Sea; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics